Derailed Democracy and Daily Dawn: A Critical Analysis of Editorials and Columns (October 1999 – August 2002) - Parveen, Saima; Zahoor, Muhammad Abrar (Journal of History Culture and Art Research, 2018)
Pakistan inherited administrative institutions from its predecessor colonial state. These institutions were highly centralized, developed over a time period of many centuries and bequeathed intact. Contrastingly, the political and representative institutions and traditions that Pakistan inherited were moribund because they could not experience smooth sailing and hence not evolved over a reasonable time span. Unfortunately political parties could not develop democratic culture which paved the way for civil and military bureaucracy to overcome established institutional structure. By holding very strong power, the institutions of civil and military bureaucracy continued to override what they found in the form of representative. The tide could not be turned and Pakistan went through more than three decades of dictatorships. Media also faced the same fate and could not play the role of healthy criticizer for government as was due on it being the fourth pillar of state. The media can play its constructive role in democracy only if there is encouraging environment that allow them to do so. Democracy and media both suffered not being in good and strong hands during this period. This research paper is an effort to explore, evaluate and analyze the role of Dawn newspaper in responding to the fourth military coup of Oct 12, 1999. The media outlet studied under this research paper is an English daily newspaper “Dawn”. It is an analysis of the role of Dawn in public opinion making, developing political consciousness among Pakistani masses and playing the role of healthy and balanced opposition for military coup of Oct 12, 1999. The findings reveal that despite the friendly behavior of Musharraf government towards media, the response of Dawn to fourth martial law of country’s history was very careful and reserve unlike other newspapers of Pakistan. Dawn not only remained stick to its policy of neutrality but also analyzed the events very critically. This research paper is a qualitative analysis of the response of Pakistan’s relatively reliable and unbiased newspaper Dawn towards the fourth military coup and political developments mainly, Provisional Constitutional Order (PCO), judicial validation of the military coup and Legal Framework Order (LFO).